2017
DOI: 10.1523/jneurosci.2079-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hebbian Spike-Timing Dependent Plasticity at the Cerebellar Input Stage

Abstract: Spike-timing-dependent plasticity (STDP) is a form of long-term synaptic plasticity exploiting the time relationship between postsynaptic action potentials (APs) and EPSPs. Surprisingly enough, very little was known about STDP in the cerebellum, although it is thought to play a critical role for learning appropriate timing of actions. We speculated that low-frequency oscillations observed in the granular layer may provide a reference for repetitive EPSP/AP phase coupling. Here we show that EPSP-spike pairing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 92 publications
2
78
0
Order By: Relevance
“…7. According to experimental estimates (see above and (Sola et al, 2004;Sgritta et al, 2017)), the GrC model was activated by 2 synapses with a higher release probability (p=0.5) for accelerating and non-adapting GrCs than for strong-adapting GrCs (p=0.1). The GrC model responses at different frequencies (Fig.7A), as well as the SFC/fstim plots (Fig.…”
Section: Computational Modelling Predicts Parameter Tuning In Grc Submentioning
confidence: 98%
See 1 more Smart Citation
“…7. According to experimental estimates (see above and (Sola et al, 2004;Sgritta et al, 2017)), the GrC model was activated by 2 synapses with a higher release probability (p=0.5) for accelerating and non-adapting GrCs than for strong-adapting GrCs (p=0.1). The GrC model responses at different frequencies (Fig.7A), as well as the SFC/fstim plots (Fig.…”
Section: Computational Modelling Predicts Parameter Tuning In Grc Submentioning
confidence: 98%
“…This specialization may be the result of plasticity causing specific pre-and post-synaptic changes rewiring the system and optimizing signal transfer (e.g. LTD may characterize low-p MFs synapses with strong-adapting GrCs, while LTP may characterize high-p MFs synapses with accelerating GrCs) (Sola et al, 2004;Sgritta et al, 2017). The relationship between these putative transmission channels and zebrin stripes (Zhou et al, 2014) and GrC functional GrC clusters (Valera et al, 2016) remains to be determined.…”
Section: Implications For Signal Recoding At the Cerebellum Input Stagementioning
confidence: 99%
“…There is experimental evidence that calls each of these predictions into question. There appears to be plasticity throughout the cerebellum, including at the mossy fibre to granule cell synapses, and within the deep cerebellar nuclei (Gao et al 2012;D'Angelo, 2014;Sgritta et al 2017;Raymond & Medina, 2018). Multi-cell recording and imaging methods have shown that very high numbers of granule cells are simultaneously active, sometimes approaching 50% at any given time Giovannucci et al 2017;Knogler et al 2017;Gilmer & Person, 2018).…”
Section: Predictions Of the Original Codon Theory Includedmentioning
confidence: 99%
“…Therefore it is not surprising to find plasticity at the mossy fibre to granule cell synapses that could either be unsupervised (reflecting the statistics of the mossy fibre inputs) or supervised (tailored to the needs of the specific functions to be approximated) (Sgritta et al . ). We note that learning a granule cell representation would be expected to increase the representational and computational power of the network (Schweighofer et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation